APPLICATION OF INTERNET TECHNOLOGY IN CREATION PHILOLOGICAL EDUCATIONAL RESOURCES - Veselov, Sergey; Kabachenko, Victor; Bolshakova, Natalia (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Philological high school education traditionally involves working with numerous literary sources. Some educational resources, such as dictionaries, are well-structured, which allows them to be translated into electronic form. For the learning process, the most promising form is a web site that provides broad resource availability, a user-friendly interface with the learner, the possibility of feedback, and effective mechanisms for information retrieval. The aim of the work is the creation of a specialized site dedicated to the electronic version of the linguistic encyclopaedic dictionary "Russian language from A to Z" [1].